Nonsevere acute otitis media: a clinical trial comparing outcomes of watchful waiting versus immediate antibiotic treatment - McCormick, David P; Chonmaitree, Tasnee; Pittman, Carmen; Saeed, Kokab; Friedman, Norman R; Uchida, Tatsuo; Baldwin, Constance D (Pediatrics (Evanston), 2005)
The widespread use of antibiotics for treatment of acute otitis media (AOM) has resulted in the emergence of multidrug-resistant pathogens that are difficult to treat. However, it has been shown that most children with nonsevere AOM recover without ABX. The objective of this study was to evaluate the safety, efficacy, acceptability, and costs of a non-ABX intervention for children with nonsevere AOM. Children 6 months to 12 years old with AOM were screened by using a novel AOM-severity screening index. Parents of children with nonsevere AOM received an educational intervention, and their children were randomized to receive either immediate antibiotics (ABX; amoxicillin plus symptom medication) or watchful waiting (WW; symptom medication only). The investigators, but not the parents, were blinded to enrollment status. Primary outcomes included parent satisfaction with AOM care, resolution of symptoms, AOM failure/recurrence, and nasopharyngeal carriage of Streptococcus pneumoniae strains resistant to ABX. Secondary outcomes included medication-related adverse events, serious adverse events, unanticipated AOM-related office and emergency department visits and telephone calls, the child's absence from day care or school resulting from AOM, the parent's absence from school or work because of their child's AOM, and costs of treatment. Subjects were defined as failing (days 0-12) or recurring (days 13-30) if they experienced a higher AOM-severity score on reexamination. A total of 223 subjects were recruited: 73% were nonwhite, 57% were <2 years old, 47% attended day care, 82% had experienced prior AOM, and 83% had not been fully immunized with heptavalent pneumococcal vaccine. One hundred twelve were randomized to ABX, and 111 were randomized to WW. Ninety-four percent of the subjects were followed to the 30-day end point. Parent satisfaction with AOM care was not different between the 2 treatment groups at either day 12 or 30. Compared with WW, symptom scores on days 1 to 10 resolved faster in subjects treated with immediate ABX. At day 12, among the immediate-ABX group, 69% of tympanic membranes and 25% of tympanograms were normal, compared with 51% of normal tympanic membranes and 10% of normal tympanograms in the WW group. Parents of children in the ABX group gave their children fewer doses of pain medication than did parents of children in the WW group. Subjects in the ABX group experienced 16% fewer failures than subjects in the WW group. Of the children in the WW group, 66% completed the study without needing ABX. Immediate ABX resulted in eradication of S pneumoniae carriage in the majority of children, but S pneumoniae strains cultured from children in the ABX group at day 12 were more likely to be multidrug-resistant than strains from children in the WW group. More ABX-related adverse events were noted in the ABX group, compared with the WW group. No serious AOM-related adverse events were observed in either group. Office and emergency department visits, phone calls, and days of work/school missed were not different between groups. Prescriptions for ABX were reduced by 73% in the WW group compared with the ABX group. Costs of ABX averaged $47.41 per subject in the ABX group and $11.43 in the WW group. Sixty-six percent of subjects in the WW group completed the study without ABX. Parent satisfaction was the same between groups regardless of treatment. Compared with WW, immediate ABX treatment was associated with decreased numbers of treatment failures and improved symptom control but increased ABX-related adverse events and a higher percent carriage of multidrug-resistant S pneumoniae strains in the nasopharynx at the day-12 visit. Key factors in implementing a WW strategy were (a) a method to classify AOM severity; (b) parent education; (c) management of AOM symptoms; (d) access to follow-up care; and (e) use of an effective ABX regimen, when needed. When these caveats are observed, WW may be an acceptable alternative to immediate ABX for some children with nonsevere AOM.